Aplikasi Virtual tour Sebagai MediaPromosi Objek Wisata di Stone Garden Kab. Bandung Barat - Yuliana, Ade; Lisdianto, Eko (Puslitbang Kopertip Indonesia, 2017)
West Java saves a lot of tourism potential that needs to be developed and managed in a professional manner through local government or a trusted third party as a manager. One of the potential of tourism, especially in Kabupaten West Bandung namely Stone Garden is located at the top of Pawon Mountain, Kampung Girimulya. Stone Garden in the Citatah Karst is a landscape which have tourism potential and strategic value Beautiful view, city view towards Padalarang and its surroundings from the top of Mount Masigit the main attraction. But the benefits and potential of such nature is not commonly known because of the lack of a media campaign depicting the attraction Stone Garden significantly so that potential tourists both domestic and abroad not optimally familiar with this attraction. From the above problem the authors designed a Virtual Tour with an attractive user interface interactive, user friendly to support and facilitate the introduction of multiple facility locations Stone Garden. With the Virtual Tour can be made easier for the manager to promote and facilitate the introduction of site locations without having to come to that location, so that the tourists whose want to know Stone Garden in detail only access the website to explore the attractions Stone Garden thoroughly. The test results calculation User Acceptance Test (UAT) data obtained feasibility of material with an average percentage of 92% included in the category of very appropriate in terms of design, features and user satisfaction. It can be concluded that the application virtual tour as a promotional medium attractions in Stone Garden Cipatat West Bandung regency, can help innovative tourism marketing and komunikastif with extensive outreach.